The Blues and the Scientific Method: Codified Cultural Schemas and Understanding Adult Cognition from a Multicultural Perspective - David F. Hemphill (Adult Education Research Conference, 1999)
Codified cultural schemas are presented as mental structures reflective of a particular culture or language that have been made public, recorded, and disseminated. The Western scientific method and the Blues are contrasted as two examples of codified cultural schemas. Analysis of such schemas that goes beyond Eurocentric structures–and beyond the modalities of language and mathematics–to include the arts and other forms of human intelligence can help us better understand adult cognition across cultures, as well as aid us in the work of adult education in multicultural societies.